The Relationship Between Postgraduates’ Emotional Intelligence and Well-Being: The Chain Mediating Effect of Social Support and Psychological Resilience - Shuo, Zhang; Xuyang, Deng; Xin, Zhao; Xuebin, Cai; Jie, Hou (Frontiers in Psychology, 2022)
Background Postgraduates usually face more life challenges than undergraduate students, including social, emotional and financial issues, and the prevalence of mental health problems in postgraduates is higher than undergraduates. Therefore, the attention on postgraduates’ mental health status is needed. Objectives The current study explored the relationship between postgraduates’ emotional intelligence and well-being by investigating the mediating effects of social support and psychological resilience and the relationship between them through the construction of a chain mediation model. Method 1,228 postgraduates completed the Emotional Intelligence Scale, the Social Support Rate Scale, the Psychological Resilience Scale, and the Subject Well-being Scale. Results There is a chain effect between postgraduates’ social support and psychological resilience mediated by their emotional intelligence and well-being, with a total effect value of 0.049. Conclusion Emotional intelligence has a predictive effect on postgraduates’ well-being. The mechanism of this effect includes the indirect effects of social support and psychological resilience. Study results revealed the relationship mechanism between emotional intelligence and postgraduates’ well-being, and provide reference for explorations of how to development postgraduates’ emotional intelligence and further improving their abilities to strengthen their emotional resilience.